The Systematic Analyses of Layered Meanings Inscribed in Interview Conversations: An Interactional Ethnographic Perspective and Its Conceptual Foundations - Skukauskaitė, Audra (Acta Paedagogica Vilnensia, 2017)
In this paper, I provide an overview of foundational sociolinguistic, critical discourse, and languacultural concepts that guide the ways interviews are conceptualized and analyzed as dynamic conversations. Interactional Ethnographic principles are introduced and then applied to the analysis of a rich point that occurred in an interview with a Lithuanian teacher of English. Analyses of the teacher’s account of her paskyrimas to a school where she worked for 32 years revealed the importance of using systematic analyses at multiple levels of scale to uncover the layers of meaning inscribed in the interview discourse. In demonstrating how my conceptual and epistemological lenses shape my analyses, I also contribute to the calls to make research more transparent and claims more grounded in analyzed evidence.